Electronic Performance System Implementation Improves State Civil Apparatus Performance Management: Implementasi E-Kinerja Dalam Meningkatkan Kinerja Aparatur Sipil Negara - Sekar Arum Puspita Ramadhani; Lailul Mursyidah; Amelia Juli Fernanda; Fadila Putri Arydianti; Lailatul Fitriah; Iis Dwi Arizqi (International Consortium of Education and Culture Research Studies, 2025)
General Background Global competition and rapid technological advancements render bureaucratic reform an imperative for government agencies in Indonesia. Specific Background E-government implementation utilizes information technology to achieve efficient, effective, and transparent governance while measuring civil apparatus performance. Knowledge Gap Despite reform efforts, apparatus comprehension varies, technological infrastructure remains uneven, and cultural adaptation requires time, often resulting in high workloads and reporting challenges. Aims This qualitative case study analyzes the implementation of the electronic performance appraisal system at MAN Sidoarjo using George C. Edwards III's theoretical framework. Results Findings demonstrate that successful system execution is supported by comprehensive communication through socialization and training, adequate infrastructure resources, positive apparatus dispositions, and supportive bureaucratic structures, though high workloads persist. Novelty This research specifically evaluates how the multidimensional synergy among communication, resource availability, staff disposition, and bureaucratic procedures governs electronic performance management execution within Islamic educational institutions. Implications Government and educational institutions must continuously enhance socialization effectiveness, provide ongoing training, and reinforce leadership support to optimize digital performance management. Highlights: Comprehensive socialization and training initiatives establish robust communication channels that facilitate independent system operation among personnel. Adequate technological infrastructure and supportive administrative server capacities provide the necessary foundation for routine reporting. Positive staff dispositions and supportive bureaucratic structures drive transparency and accountability despite heavy administrative workloads. Keywords: Electronic Performance, Policy Implementation, Performance Management, Bureaucratic Structure, State Civil Apparatus